Study of Composition and Potential of Production Forest Vegetation in the KPHP Dampelas Tinombo Area Pariasanagung Village Dampelas District Donggala District - Andi Sahri Alam; Imran Rachman; Erniwati; Hendra Pribadi (Postgraduate, University of Mataram, 2023)
Forests, as a gift and mandate from Almighty God, which were bestowed upon the Indonesian nation, are a natural wealth that is priceless, therefore we must be grateful for it. This research was carried out for 3 months, from June to September 2021. This research was located in a production forest in the Dampelas Tinombo Model KPHP area, which is included in the Parisian Agung Village area, Dampelas District, Donggala Regency, Central Sulawesi Province. The composition of vegetation types in the production forest of Parisian Agung Village consists of 28 types of vegetation. at the tree level in the plot there were 165 individuals from 25 types of vegetation, while at the pole level vegetation, there were 140 individuals from 25 types of vegetation, at the sapling level there were 145 individuals from 28 types of vegetation and at the seedling level there were 154 individuals from 28 types of vegetation. While the potential volume of trees in the observation plot is 162.53 m3 from 165 individuals, the bayas type has the largest volume with 13.17 m3 and the pole level volume in the observation plot is 17.89 m3 from 140 individuals, the prupuk type has the largest with 1.63 m3.